Improvement of level MDA and SOD Using of Ganoderma Lucidum as Adjunctive Treatment for Statin Based Therapy in High Risk Patient Based on Framingham Score - vitriyaturrida vitriyaturrida; M Saifur Rohman; Djanggan Sargowo; Dadang Hendrawan (The Indonesian Heart Association, 2018)
It is well known from previous research on the importance of antioxidants to inhibit the progression of coronary heart disease in high-risk patients based on framingham scores. Statins are routinely administered in high-risk patients based on the Dyslipidemia 2016 ESC guidelines but the effects of adding Ganoderma are known to have antioxidant effects, in patients who have received statins. This study aims to assess the effect of antioxidants through measurement of SOD and MDA in patients given a combination of Ganoderma lucidum with statins.Method: A total of 24 patients with high-risk patients based on the Framingham score > 20% were selected as sample of study. Patients with respondents who had never received statin therapy or ACEi or ARB or CCB or beta blocker, or did not routinely consume the drug for 2 weeks were excluded from this study. The addition of Ganoderma lucidum dose of 3x250 mg was added to statins as the first group and Ganoderma lucidum dose of 3x250 mg was added to the Statin combination of Angiotensin Converting Enzym inhibitors (ACE inhibitors) or Angiotensin Receptor Blockers (ARB) and or Calcium Channel Blockers (CCB) and or Beta blockers as second group for 90 days. SOD and MDA levels were measured before and after the administration of Ganoderma Lucidum with the ELISA method.Result: After the administration of Ganoderma Lucidum with standard therapy, there was a decrease in MDA levels and an increase in SOD levels after 90 days in two groups. Conclusion: The addition of Ganoderma Lucidum to standard therapy can reduce oxidant levels in high-risk patients based on framingham scores. Keyword: Superoxyde-dismutase, Malondyaldehide, Oxidative Stress, Antioxidant, Ganoderma Lucidum, Statin